Tourism Industry of Kashmir (1947-1989) - Itoo, Mushtaq Ahmad (International Journal of Management and Sustainability, 2013)
Tourism is one of the vital sectors of Kashmir economy. Though this industry emerged in modern sense during nineteenth century but it flourished after 1947 with the establishment of popular government and subsequent change in the nature of state. Also the various plans were framed and implemented for the promotion of this industry. The present paper highlights the historical development of tourism industry and the causes responsible for its vicissitudes during the period under reference. Data has been collected from the department of tourism, Jammu & Kashmir Govt. The statistical data of the tourism industry reveals that the tourism industry in Kashmir saw a great progress and reached to its full boom in the eighties of the twentieth century, though the industry saw many ups and downs during this period.